Nutrient harvest and soil fertility as influenced by legume-wheat (Triticum aestivum) sequences - PARSAD, N K; KUMAR, SANJAY (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1993-95 to assess the contribution of preceding legume crop on succeedingwheat (Triticum aestivum L. emend. Fiori & Paol) for crop production, nutrient harvest and balance of the same in soilunder recommended doses of nutrients of kharif crops and variable levels of nitrogen to succeeding wheat. Blackgramphasea/us mango L.) as a preceding crop to wheat resulted in the maximum wheat production while stylo (Stylosantheshamata L.) wheat sequence accounted for higher wheat equivalent yield. Application of 75 kg N/ha to wheat grownafter legume was as good as to wheat yield received at 100 kg N/ha after legume. Soybean (Glycine max (L.) Merr.)wheatsequence has removed the maximum quantity ofN while wheat grown after blackgram harvested the maximumquantity of N. Soybean - wheat sequence further removed the highest quantity of P but stylo - wheat sequence recordedthe maximum recovery of K. Though all the legume - wheat sequences have recorded better build up in soil N,however, wheat grown after blackgram at 100 kg N/ha recorded the maximum build up in available soil N while wheatgrown in absence of extemal N has left over maximum available P in soil. General increase in available K was noticedunder all the sequences to their initial status.